Sebaran Kerang Anadara granosa Berdasarkan Kelas Ukuran Terhadap Logam Berat Cr (Chromium) Di Perairan Pantai Semarang Bagian Timur - Feriano, Hafidz; Suryono, Chrisna Adi; Yulianto, Bambang (977-2407769)
Anadara granosais one of bivalve species, which lives in the bottom of marine waters it has a long life cycle. This species is commonly used as bioindicator in the assessment of water quality. The variety of human activities, such as settlements, ports, industries, and fishing coastal areas cause a decrease in water quality which directly affect the presence and abudance of mussels in the waters.The aimed was research to determine the relationship between the heavy metal concentration of Cr (Chromium) and size class distribution of the blood mussels (A. granosa) at Eastern Semarang Coastal Waters.The research was conducted from March to April 2012 at 8 stations in Eastern Semarang coastal waters, Semarang Central Java. The method of the research was case study with descriptive data analysis. Sampling locations were determined by purposive sampling methode.The results showed that the lowest heavy metal concentrations of Cr (Chromium) were found at Station III and IV, in front of estuaries of Benger River. They were are 13,92 mg/l for Station III and 19,60 mg/l for Station IV. The highest number of A.granosa were also found at Station III and Station IV, which was 56 and 130. The distribution pattern of A. granosa at the research locations showed a clumped pattern, and the A.granosa most dominant size found in medium class (2-3Cm).